Efektifitas Pembelajaran Matematika Model Kooperatif Jigsaw dengan Pendekatan Matematisasi Berjenjang dan Tanapa Pendekatan Matematisasi Berjenjang Ditinjau dari Motivasi Belajar dan Inteligensi Siswa pada Siswa SMA di Kota Madiun - Sardulo Gembong (Jurnal Pendidikan, 2010)
This research serves analyses on: 1) which brings about better result of learning mathematics between Jigsaw Cooperative Model with and without Stratified Mathematication Approach,                      2) students’ achievement in mathematics under Jigsaw Cooperative Model with and without Stratified Mathematication Approach in consideration of both students’ motivation and intelligence, 3) what different achievement made by students with high, medium and low learning motivation under Jigsaw Cooperative Model with and without Stratified Mathematication Approach, 4) what different achievement made by students with high, medium and low intelligence under Jigsaw Cooperative Model with and without Stratified Mathematication Approach.             The population of the reseaech are all state SMA-s in Madiun Municipality, term 2007/2008 which consist of 6 SMA-s. The sample is drawn under random sampling technique. The sample was drawn one class for experiment one, and one class for control one out of students of SMA Negeri I Madiun , and one class for experiment one, and one class for control one out of students of SMA Negeri VI  Madiun. The samples consist of 148 students. Instruments are analytically attested at SMA V Madiun with 74 respondents.             The analysis brings about conclusions as follows: 1) the students who learn mathematics under Jigsaw Cooperative Model with Stratified Mathematication Approach made better achievement than those without Stratified Mathematication Approach, both in general consideration and in consideration of each level of motivation and intelligence category, 2) students with high motivation made better achievement than those with medium one, and the students with medium motivation strength made better achievement than those with low one, both in general consideration and in consideration of each learning model given, 3) students with high intelligence made better achievement than those with medium one, and the students with medium motivation strenght made better achievement than those with low one both, in general consideration and in consideration of each learning model given, 4) In consideration of the students’ motivation, intelligence and learning model, the Jigsaw Cooperative Model with Stratified Mathe-matication Approach results in better students’ achievement than that without Stratified Mathematication Approach.